Comparative Study of Olopatadine Hydrochloride 0.1% and Emedastine difumarate 0.05% Comparing their Clinical Efficacy and Adverse Effects in Allergic Conjunctivitis (Medical Forum Monthly, 2024)
Objective: To assess the efficacy and adverse effects of 0.1% Olopatadine hydrochloride (OHC) and compare them to 0.05% Emedastine difumarate (ED) in the treatment of allergic conjunctivitis.Study Design: Prospective and comparative studyPlace and Duration of Study: The study was conducted at Islam Teaching Hospital, Islam Medical College, Sialkot from February 2013 to June 2014.Materials and Methods: 74 adult patients including 35 male patients aged 21- 47 years ( Average 32.39) and 39 females aged 20 - 42 years (Average 31.8) some with a history of systemic allergic manifestation (e.g. asthma, dermatitis, or bronchitis) along with sign and symptoms of allergic conjunctivitis were enrolled in the study. At the time of induction, manifestations of allergic conjunctivitis (mucous discharge, itching, conjunctival congestion, chemosis, and watering) were present. Patients were allocate at random to either of the 2 groups, A and B. The patients in the Group A, (n = 36) received OHC and those in the Group B (n = 38) were treated with ED. The dose in Group A was one drop in both the eyes 12 hourly. Group B received one drop in both the eyes 6 hourly. The study was started on the first patient visit, when after the diagnosis; the drug was administered. Patients from both the groups were re-evaluated half an hour, forty eight hours, seven and fourteen days later. Efficacy and side effects in both the groups were assessed. The severity of signs and symptoms were assigned a score from 0 - 3. The results were analysed using independent sample T test.Results: At the start of the study, cumulative score of the patient's sign and symptoms was calculated, with a mean value of 7.31 for group A and 7.38 for group B. There was no significant statistical disparity between the groups (p = 0.88). The cumulative scores at the end of study on day fourteen were 0.72 for group A and 1.0 for group B. This was also statistically not significant (p = 0.15) but Olopatadine was noted to be more effective.The side effects of both the medicines were similarly assessed with cumulative scores calculated at each follow up. In group A, there were minimal side effects with mean cumulative score on the final visit was 0.25 in group A and 0.54 in Group B, with statistically significant (p = 0.015) difference.Conclusion: Olopatadine was discovered to have better efficacy (not statistically significant) and less adverse effects (statistically significant) than Emedastine.